2013
DOI: 10.1007/s40273-012-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Cost Effectiveness of Herpes Zoster Vaccination

Abstract: Model input parameters such as age at vaccination, vaccine costs, HZ incidence, PHN length and duration of vaccine efficacy had a great impact on the estimated cost effectiveness of HZ vaccination. To compare the results of different cost-effectiveness studies of HZ vaccination, uniform methods should be used and the most important input parameters used for the different models should be critically assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 38 publications
5
51
0
Order By: Relevance
“…These findings are consistent with other reviews summarizing evidence on the cost-effectiveness of HZ vaccination. 15,49 However, compared with the review of Szucz et al, 49 three more studies were included. Moreover, this review contains more specific data on the clinical results found in the studies, the influence of the modeling of vaccine efficacy on cost-effectiveness results and the optimum age of vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with other reviews summarizing evidence on the cost-effectiveness of HZ vaccination. 15,49 However, compared with the review of Szucz et al, 49 three more studies were included. Moreover, this review contains more specific data on the clinical results found in the studies, the influence of the modeling of vaccine efficacy on cost-effectiveness results and the optimum age of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43][44][45][46][47] In addition, two studies performed a multiway sensitivity analysis 37,45 and nine studies a probabilistic sensitivity analysis (PSA). 35,[37][38][39][40][41][42][43]46 Quality assessment A review of Szucs et al 49 evaluated the quality of 11 of the included studies using the British Medical Journal (BMJ)'s checklist by Drummond and Jefferson 50 and the "Quality of Health Economic Studies" evaluation tool by Ofman et al 51 Szucs et al 49 concluded that the quality of these studies varied from 'Moderate' 37,38,4337,38,43 to 'Moderate-Good' 35,36,[39][40][41][42]44 . We assessed the three other included studies using the same criteria as Szucs et al 49 used.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Although the mathematical models and the assumptions are different, these studies demonstrate clearly that the HZ vaccination in the elderly population has a favorable economic profile. Vaccination could have a significant impact on HZ disease and, above all, results a very good investment for NHS and Society.…”
Section: Discussionmentioning
confidence: 94%